Design and development of a novel spherical UAV - Malandrakis, Konstantinos; Dixon, Roland; Savvaris, Al; Tsourdos, Antonios (Elsevier, 2016)
This paper presents the design and system integration of a novel coaxial, flap actuated, spherical UAV for operations in complex environments, such as buildings, caves or tunnels. The spherical design protects the inner components of the vehicle and allows the UAV to roll along the floor if the environment permits. Furthermore, the UAV can land and takeoff from any orientation and come into contact with objects without putting the propellers at risk. Flaps at the base of the sphere will generate roll and pitch moments as opposed to conventional swash plate designs while the coaxial setup will provide the necessary yaw moments and increase in thrust to volume ratio of the system. The flaps, placed below the propellers allow for decoupled roll and pitch control in a thrust vectoring manner. The final result of this design is a well-protected, compact, easily controlled, flexible and agile UAV for operations in complex environments. The spherical UAV was successfully flight tested on a number of occasions with various PD and µ-synthesis robust control systems and was observed to be easily stabilised and resistant to external disturbances to certain extent.
Keywords: Complex environments; spherical frame; robust control; µ-synthesis; contra rotating propellers; ultra-sonic sensor; test bench; coaxial rotor